Estudio de prefactibilidad para la implementación de una planta de producción de aceite de Sacha Inchi (Plukenetia Volubilis) - Gómez de la Torre Cateriano, Lourdes (2015)
This project presents the preliminary study for a production plant of Sacha Inchi Oil (Plukenetia Volubilis). To determine if the project is viable, we made an arduous market study. We used these results in addition to the reference of its substitute product the Olive Oil to determine the demand. To obtain the information, it was used a lot of databases, among them Euromonitor, Ipsos Apoyo, among others. In addition, a study to determine the size and location of the plant in Peru was made, using tools learned in the course of Industrial Engineering, as Guerchet, “Ranking de factores”, layouts and others. These methods, which were very helpful to determine the place of location and adequate size of the plant, also help us optimize the space needed, the proximity of machinery and optimize production costs.